Identification of historic landscape features and settlement mounds in the Western Nile Delta by means of remote sensing time series analysis and the evaluation of vegetation characteristics. (December 2017) - Ginau, A.; Schiestl, R.; Kern, F.; Wunderlich, J.
Abstract: Remote sensing techniques gain increasing importance in landscape archaeological research. Traditional archaeological excavation techniques are slow and time in the Nile Delta is running out. The Nile Delta has been settled and used for agricultural cultivation since the Neolithic period and is shaped by the interplay of urbanization and agriculture. In particular, the study of ancient settlement mounds (tells) and landscape archaeological features such as former river channels requires urgent action. This study seeks to develop supervised classification techniques on the basis of multitemporal Landsat 8 images to easily monitor existing high tells in the Delta that have not been destroyed yet. In the 19th and early 20th centuries many tells were destroyed, because tell sediments (sebakh) were harvested on an industrial scale in order to be used as fertilizer. These activities continued on a smaller scale into the mid to later 20th century. Geochemical analysis of ancient settlement material (sebakh) has confirmed the high content of nutrients. In a second step which is based on these geochemical findings, we seek to identify the category of lost tells which had been transformed into agricultural areas. We suggest that the presence of ancient settlement material enhances the overall vegetation performance and indirectly allows identification of lost tells via describing the vegetation performance. In general, the vegetation performance is a new measure and invented within this study. It is calculated as the product of different measures describing the plant growth, namely the mean NDVI (Normalized Difference Vegetation Index), growth statistics and crop rotations derived from a large set of multitemporal NDVI images. Our results show that there exists a relationship between vegetation performance and the appearance of archaeological material in the topsoil and such information can be useful for planning of non-invasive archaeological surveys. Remarkably the vegetation performance corresponds with the location of former Nile branches that are currently investigated by the authors on the basis of TandemX elevation data and sedimentological investigations of the area. Several factors such as water availability and salinity also affect plant growth and mask this relationship. Additionally, our methods to describe the number of crop rotations or growth statistics from NDVI time series help to analyse the agricultural areas in the Nile Delta. Therefore, the methods used in this study may offer important insights on aspects of urban sprawl and agricultural areas in the Nile Delta and beyond. Highlights: Methods for the identification and mapping of different classes of tells in the Nile Delta are presented. Identification of lost tells via analyzing plant growth in NDVI time series is of high interest and innovative. New links between plant growth and the presence of ancient settlement material in the topsoil are remotely tangible. High vegetation performances measured today also result from deposition of nutritious Nile mud of former palaeo-rivers.